Improving the mechanical and thermal properties of hemp concrete by treating the hemp hurds with sodium hydroxide solution. Issue 1 (1st April 2022) - Adam, L; Isopescu, D N; Maxineasa, S G
Abstract: The objectives of the research were to analyse how the treatment with sodium hydroxide solution of hemp stems influences the mechanical and thermal behaviours of concrete when hemp stems are used in the composition of concrete. Tests were performed on hemp concrete samples to evaluate the density and measure the heat transfer coefficient, compressive strength and modulus of elasticity. The activities carried out aimed to identify the influence of the sodium hydroxide solution concentration on the variations of the measured parameters and expressing some conclusions regarding the need to treat the hemp stems before their use in concrete. The need for research is given by the nowadays demand for obtaining eco-sustainable construction materials, in which the possibility of using a material that is considered plant waste becomes an economic resource in a circular economy.